Host-based detection and analysis of Android malware: implication for privilege exploitation - Ashawa, Moses; Morris, Sarah (Infonomics Society, 2019)
The Rapid expansion of mobile Operating Systems has created a proportional development in Android malware infection targeting Android which is the most widely used mobile OS. factors such Android open source platform, low-cost influence the interest of malware writers targeting this mobile OS. Though there are a lot of anti-virus programs for malware detection designed with varying degrees of signatures for this purpose, many don’t give analysis of what the malware does. Some anti-virus engines give clearance during installations of repackaged malicious applications without detection. This paper collected 28 Android malware family samples with a total of 163 sample dataset. A general analysis of the entire sample dataset was created given credence to their individual family samples and year discovered. A general detection and classification of the Android malware corpus was performed using K-means clustering algorithm. Detection rules were written with five major functions for automatic scanning, signature enablement, quarantine and reporting the scan results. The LMD was able to scan a file size of 2048mb and report accurately whether the file is benign or malicious. The K-means clustering algorithm used was set to 5 iteration training phases and was able to classify accurately the malware corpus into benign and malicious files. The obtained result shows that some Android families exploit potential privileges on mobile devices. Information leakage from the victim’s device without consent and payload deposits are some of the results obtained. The result calls proactive measures rather than proactive in tackling malware infection on Android based mobile devices.